Exposure To Ai Content And The Rationalisation of Digital Privacy Abuse: A Study Among Students at University X in Pekanbaru - Sa’diyah Aristawati Septini; Fakhri Usmita (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The rapid development of generative Artificial Intelligence (AI) has triggered the